The Impact of Lead Levels in Blood on Blood Pressure, Body Mass Index, and Hand Strength in Rice Farmers” - Noviana Zahrotul Mufidah; Putri Citra Rahmawati; Regita Agnesya Putri; Indah Tri Susilowati (GLOBAL HEALTH SCIENCE GROUP, 2026)
Lead contamination in pesticides poses a serious threat to health due to its bioaccumulative and toxic properties to various organ systems, including the nervous, hormonal, and cardiovascular systems. This study aims to determine the relationship between blood lead levels and blood pressure, body mass index (BMI), and handgrip strength in rice farmers in Tlingsing Village, Cawas District, Klaten Regency. This analytical study used a cross-sectional design with a sample of 24 rice farmers. Venous blood samples were taken using 3 cc EDTA vacuum tubes and examined for lead levels using the Graphite Furnace Atomic Absorption Spectrophotometry (GFAAS) method at BBLK Yogyakarta. Blood pressure was measured using an Omron 7120 digital sphygmomanometer, BMI using a HN 289 digital scale and a GEA SH2A stature meter, and hand strength using a Camry EH101 electronic hand dynamometer. Data analysis was carried out using a bivariate correlation test at a 95% confidence level (p=0.05). The results showed that blood lead levels were significantly associated with blood pressure (p=0.028), with a percentage of stage 1 hypertension of 50.0% and hypertensive crisis of 45.8%. Lead levels were not significantly associated with BMI (p=0.082), with 29.2% of participants classified as overweight and 8.3% as obese. There was no significant association with hand grip strength (p=0.360), with 20.8% of participants classified as having medium strength and 33.3% as having low strength.